WAQF MANAGEMENT FOR EDUCATION IN SMK IT SMART INFORMATIKA (Case Study at Solo Peduli Foundation) - Ardi Arman Syahada; Yusdi Haq (JURNAL HAKAM, 2025)
Waqf is a practice that is recommended by Islamic shari'a because it has many virtues in it. The purpose of waqf is to provide benefits from the property that is channeled for the good of the people. 'The purpose of this research is to find out related to the Management of Waqf for Educational Institutions at Smart Informatika Integrated Islamic Vocational School located in Banyuanyar, Banjarsari, Surakarta. The method used is qualitative with a descriptive approach of analysis. The activity carried out by the researcher is to conduct interviews with the administrators of the social institution concerned in addition to collecting data from various literature, articles, journals, and sites on the internet related to the focus of the research. The data source was obtained from primary data sourced from field studies at the Solo Peduli Foundation. Meanwhile, secondary data is obtained from various sources that contain various matters related to waqf management. Efforts made by the Solo Peduli Foundation in managing waqf in the field of education include: in obtaining waqf assets by making invitations on social media and holding social activity events; In transparency related to the use of waqf assets, namely by providing periodic reports related to the development of waqf management. The impact felt from the existence of a school built from waqf assets is: for waqf recipients: get jariyah rewards; for the community: creating jobs and reducing poverty rates; For students: Obtain a proper education and improve skills to be ready for work.